Skin Hypersensitivity and Precipitating Antibodies Against Allergic Bronchopulmonary Aspergillosis - Amtul Naseer; Hafiz UL Huda; Khalida Naseem (ASEAN Journal of Science and Engineering, 2021)
Allergic bronchopulmonary aspergillosis (ABPA) is a very fatal disease and more than four million people have been affected. We collected data of forty-five patients and a skin hypersensitivity test was performed. We also evaluated precipitating antibodies against Aspergillus fumigatus. Instant hypersensitivity reactions were recorded in 22.22% of patients and 6.66% displayed delayed type III reaction. 4.44% of patients exhibited precipitin bands and three infections of ABPA among 45 infected people. A literature survey was also made to understand Aspergillus fumigatus.